2009
DOI: 10.1016/j.bcp.2009.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Species differences in pharmacokinetic and pharmacodynamic properties of nebicapone

Abstract: The present study was designed to characterize pharmacodynamic and pharmacokinetic properties of nebicapone in rats and mice. Upon oral administration of nebicapone the extent of mouse liver catechol-O-methyltransferase (COMT) inhibition is half that in the rat.Nebicapone was rapidly absorbed reaching plasma C max within 30 min and being completely eliminated by 8 h. Nebicapone was metabolized mainly by glucuronidation and methylation in both species, but rat had an extra major metabolite, resulting from sulph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The HLMs or human expressed UGT enzymes were employed for kinetic studies at concentrations ranging from 0.0021 mg/mL to 0.0053 mg/mL. The rates of the glucuronidation were fitted to the following equations: Where V (nmol/mg/min) is the rates of the glucuronidation, C metabolite (μM) and C protein (mg/mL) respectively are the concentration of the metabolite and the reaction protein, t (min) is the reaction time [2,22]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HLMs or human expressed UGT enzymes were employed for kinetic studies at concentrations ranging from 0.0021 mg/mL to 0.0053 mg/mL. The rates of the glucuronidation were fitted to the following equations: Where V (nmol/mg/min) is the rates of the glucuronidation, C metabolite (μM) and C protein (mg/mL) respectively are the concentration of the metabolite and the reaction protein, t (min) is the reaction time [2,22]. …”
Section: Methodsmentioning
confidence: 99%
“…It exhibits a wide range of pharmacological effects, including antioxidation, anti-inflammation, and anticarcinogenic activity [2,3]. A study reported that after luteolin’s oral administration, it undergoes methylation as a major metabolic pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Liver, kidney, small intestine (jejunum), and lung tissue homogenates were prepared as described previously (Bonifácio et al, 2009). In brief, six male Sprague-Dawley rats were sacrificed by cervical dislocation after fasting for 12 h. Tissues (liver, kidney, small intestine, and lung) were homogenized in phosphate buffer (5 mM, pH 7.4) and then were centrifuged at 15,000g for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…The COMT reaction was performed as described previously with some modifications (Bonifácio et al, 2009). In brief, the reaction mixture containing homogenate protein (1.0 mg/ml), 100 M MgCl 2 , 1.0 mM EGTA, and 20 M luteolin, with or without 30 nM entacapone in 150 l of phosphate buffer (5 mM, pH 7.8), was preincubated for 3 min at 37°C, and then 1.5 l of 25 mM S-adenosylmethionine dissolved in phosphate buffer (5 mM, pH 7.8) was added to initiated the reaction.…”
Section: Methylation Of Luteolin In Rat Tissuementioning
confidence: 99%
“…The rat is the most frequently employed species for pharmacokinetic and pharmacodynamic nonclinical studies with COMT inhibitors (Wikberg and Taskinen, ; Wikberg et al ., ; Vieira‐Coelho and Soares‐da‐Silva, ; Parada et al ., ; Forsberg et al ., ; Soares‐da‐Silva et al ., ; Bonifácio et al ., ; Sun et al ., ) and, therefore, we selected it as the most relevant animal model. To the best of our knowledge, there are only two liquid chromatographic techniques published to quantify opicapone and its active metabolite (BIA 9–1079; Almeida et al ., ; Gonçalves et al ., ).…”
Section: Introductionmentioning
confidence: 99%